Relationship between NYHA degrees and Self-efficacy with Quality of Life in Heart Failure Patients: A Cross-Sectional Study (International Journal of Nursing Education, 2022)
Heart failure causes functional limitations that result in fatigue and dyspnea, thereby reducing the quality of life. Various factors related to the quality of life of heart failure patients include NYHA degree and self-efficacy. An increase in the number of heart failure patients treated at the Aceh Government Hospital occurred in 2021, patients also often experienced repeated hospitalizations. This study aims to determine the relationship between patient NYHA degree and self-efficacy with the quality of life of patients with heart failure. This type of research is quantitative with a cross-sectional study on 154 heart failure patients. Instruments to measure self-efficacy using Cardiac Self-Efficacy (CSE) and quality of life with the Minnesota Living with Heart Failure (MLHF) questionnaire. Bivariate analysis using chi-square and multivariate analysis with logistic regression. The results showed a significant relationship between NYHA degree and self-efficacy with quality of life (p<0.05). The results of the multivariate analysis found that the degree of NYHA was the most dominant factor associated with the quality of life of heart failure patients with an Odds Ratio (OR) of 17.438. The quality of life of heart failure patients is strongly influenced by the degree of NYHA, lowering the degree of NYHA is the best step to prevent a decrease in the quality of life of patients with heart failure.